Study on students' awareness and understanding on plagiarism / Noor Ayesha Mohd Ezanee - Mohd Ezanee, Noor Ayesha (2008)
Plagiarism can be said as the offences as to mislead, or in other words, lying. The study also would want to understand students' understanding and perception on the term plagiarism itself. The study will find reasons or factors that lead the students to plagiarize, or if they did not know the term, it is the same as copy-and-pasting. These reasons or factors must be overcome, and that the faculty should do something about it.